Feasibility study of the application of a cooling energy storage system in a chiller plant of an office building located in Santiago, Chile. (June 2019) - Venegas-Troncoso, Tomás; Ugarte-Larraguibel, Gaspar; Vasco, Diego A.; Rouault, Fabien; Pérez, Rodrigo
Abstract : LHTES system was implemented along with a conventional chiller system of a building. Strategies of operation were assessed by computational simulation with EnergyPlus. A hybrid operation strategy was evaluated, and the cooling loads were obtained. LHTES reduces by 7.8% the cooling energy consumption of the cooling system. Abstract: Energy consumption of commercial buildings has increasingly gained attention worldwide, because of its significant electricity consumption and peak power demand. Chiller plants are mostly used in commercial buildings to generate cold water for air conditioning. However, because the chiller plants and the refrigeration systems tend to be oversized with respect to their critical design load conditions, they certainly lead to higher energy consumption than a properly sized chiller plant. One possible way to reduce the power consumption and redistribute energy use is through the integration of latent heat thermal energy storage (LHTES) systems with air-cooling system in buildings. In the present work, a LHTES system based on ice is implemented along with a conventional chiller system of an existing commercial building located in Santiago, Chile. Different strategies of operation in a design day are assessed by computational simulation with EnergyPlus. A hybrid operation strategy is evaluated for the hottest summer week, and the results of the cooling loads are obtained. Finally, we founded that the implementation of a LHTES reduces by 7.8% the cooling energy consumption of the cooling system during the analyzed period.